Permutações caóticas e aplicações - Santos Júnior, Edson Praxedes dos (2014)
This study aimed to systematize a formula that gives the number of chaotic permutations of n objects by means of the principle of inclusion and exclusion. To do so, are developed and validated, throughout the text, basic and advanced tools of combinatorics. There is also a section devoted to problems which can be solved by the formula outa obtained and in which approaches the formula for obtaining the number of chaotic permutations by means of recurrence.